KEY LEXEMES AND KEY CONCEPTS OF MATAPOETICAL DISCOURSE OF G. APOLLINAIRE - Vyacheslav P. Khodus; Roza V. Chvalun (Вестник Северо-Кавказского федерального университета)
This article gives an analysis of metapoetical discourse of G. Apollinaire in its development, we determined key lexemes which compose key concepts of metapoetical discourse, and it gives us an opportunity to disclose the intentions of the author concerning the creation of non-linear poetical texts (calligrammes).